Pokémon. Sun & Moon. 8 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2020)
Sun and Moon have very different goals in life, and their lives are turned upside down after they meet each other. When the Ultra Beasts attack, the two must gain control of Legendary Pokémon Solgaleo and Lunala in order to stop them. After Sun's great-grandfather dies, Sun and Moon must stop Faba from taking over the Aether Foundation and destroying the island.